TO THE QUESTION ON USING OF MEASURES ON ENERGY-SAVING AT PRODUCTION OF BAR ON MILL 320 OF RUP «BMZ» - V. G. Razdobreev; P. V. Tomakov; V. A. Lutsenko; A. A. Sotnikov; P. A. Bobkov; M. I. Titov (Литьë и металлургия)
Investigations of energy-power parameters of rolling of reinforcing rolled metal of slugs of increased section are carried put. Some measures on energy-saving at production of bar on mill 320 of RUP «BMZ» are given.